Preparation of phosphotungstic acid based poly(ionic liquid) and its application to esterification of palmitic acid. (April 2019) - Wang, Yongqiang; Zhao, Dan; Chen, Guanyi; Liu, Shejiang; Ji, Na; Ding, Hui; Fu, Jianfeng
Abstract: For biodiesel production from waste cooking oils with high acid values, an inefficient esterification pretreatment is always conducted to convert free fatty acids (FFAs) before alkali-catalysed transesterification process. In this paper, phosphotungstic acid based poly(ionic liquid) was prepared to catalyse the esterification of palmitic acid with methanol while the required catalyst dosage was much lower than commercial Amberlyst-15. And the catalyst was characterized by 31 P CP-MAS NMR, FTIR, SEM, XRF and TG. Among the three poly(ionic liquid)s prepared in this paper, phosphotungstic acid based poly(ionic liquid) was selected to be the most suitable catalyst for esterification because the catalyst could be reused for more than 5 times without significant deactivation. According to single factor analyses, the esterification yield could reach 91.6% after 8 h while the reaction temperature, methanol to acid molar ratio and catalyst dosage were 65 °C, 6 and 3% wt, respectively. Afterwards, palmitic acid was proposed to be first adsorbed on the catalyst before reacting with methanol. Finally, a palmitic acid adsorbed Eley-Rideal model was employed to analyse the reaction and the adsorption mechanism was assumed as well. Graphical abstract: Image 1 Highlights: A novel method was employed to support phosphotungstic acid based ionic liquid. Phosphotungstic acid was mainly immobilized through stable chemical effects. A high esterification yield of 91.6% was obtained under mild conditions. The catalyst can be recovered conveniently and reused for more than 5 times. Eley-Rideal model was employed to analyse the reaction.